2021
DOI: 10.3390/v13102055
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming of Nasal Airway Epithelial Cells Following Infant Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is a seasonal mucosal pathogen that infects the ciliated respiratory epithelium and results in the most severe morbidity in the first six months of life. RSV is a common cause of acute respiratory infection during infancy and is an important early-life risk factor strongly associated with asthma development. While this association has been repeatedly demonstrated, limited progress has been made on the mechanistic understanding in humans of the contribution of infant RSV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Furthermore, the glycolytic flux may have subsequently entered the TCA cycle, as the citrate (Cit) and isocitrate (Ict) were both increased 30 min after tracer injection ( Figures 5A, B ). Respiratory syncytial virus (RSV) infection caused a greater glycolytic flux being dedicated to the pentose phosphate pathway and TCA cycle ( 41 ). The fate of glycolysis differed in hepatitis B virus (HBV) infection; in that case, glucose was incorporated into the pentose phosphate pathway and hexosamine biosynthesis rather than TCA cycle ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the glycolytic flux may have subsequently entered the TCA cycle, as the citrate (Cit) and isocitrate (Ict) were both increased 30 min after tracer injection ( Figures 5A, B ). Respiratory syncytial virus (RSV) infection caused a greater glycolytic flux being dedicated to the pentose phosphate pathway and TCA cycle ( 41 ). The fate of glycolysis differed in hepatitis B virus (HBV) infection; in that case, glucose was incorporated into the pentose phosphate pathway and hexosamine biosynthesis rather than TCA cycle ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that strains harbouring G protein p.E123K/D and p.P218T/S/L variants are cleared more slowly and foster an immune environment of low-level chronic stimulation or exhaustion. We previously demonstrated that infants infected with RSV in their first year of life have dampened subsequent antiviral immune responses in early childhood [49] as well as changes in airway epithelial cell metabolism [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that strains harbouring G protein p.E123K/D and p.P218T/S/L variants are cleared more slowly and foster an immune environment of low-level chronic stimulation or exhaustion. We previously demonstrated that infants infected with RSV in their first year of life have dampened subsequent antiviral immune responses in early childhood [36] as well as changes in airway epithelial cell metabolism [37]. Altered immune responses are expected in extended infections by G protein variant strains [35], and we observed differences in the acute antiviral response between subjects with resolved and prolonged infection, specifically increased levels of types 1 and 2 IFN in nasal secretions; however, we could not make causal inference about variant sequences because of confounding by co-linearity of these polymorphisms with RSV antigenic group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been observed that RSV replication upregulates glucose influx, induces aerobic glycolysis and increases lactic acid generation in epithelial cells. These metabolic adaptations may aid in enhanced nucleoside synthesis and energy needs for viral replication [ 25 , 26 ]. We have extended this work with our finding that RSV infection induces the hexosamine biosynthetic pathway (HBP) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%